Pesantren dalam Kebijakan Pendidikan Indonesia - Badrudin Badrudin; Yedi Purwanto; Chairil N Siregar (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2017)
Pesantrens are often said to have received discriminatory treatment in Indonesian education politics, despite the fact that pesantrens have contributed positively to the development of education in Indonesia. But how is the Government's policy towards pesantren in Indonesia after Indonesia's independence? This article discusses this issue based on recent research results using a political (policy) and historical approach with descriptive methods. The technique of data collection is developed by documentation study on education policy in Indonesia, observation, as well as interviews. The study proves that the Government has dominated the policy towards pesantren where the pesantren policy is approved, accepted and implemented by government institutions. The research also concludes that since the inclusion of pesantren into By Law No. 20 Year 2003 on Indonesia’s National Education System, pesantren is in a vortex of attraction and interest between society and the Government. Pesantrens are treated discriminatively by the Government characterized by unclear implementation, regulation and budget allocation for these pesantrens. In essence, Pesantrens have not received the proper attention from the Government.Keywords: policy, education, pesantren, IndonesiaPesantren sering dikatakan mendapatkan perlakuan diskriminatif dalam politik pendidikan Indonesia, walaupun pesantren telah berkontribusi positif pada perkembangan pendidikan di Indonesia. Tapi bagaimanakah sebenarnya kebijakan Pemerintah terhadap pesantren di Indonesia setelah Indonesia merdeka? Artikel ini membahas isu ini berdasarkan hasil penelitian yang menggunakan pendekatan politik (kebijakan) dan sejarah dengan metode deskriptif. Teknik Pengumpulan data dilakukan dengan studi dokumentasi terhadap kebijakan pendidikan di Indonesia, observasi, dan juga wawancara. Penelitian membuktikan bahwa Pemerintah telah mendominasi kebijakan terhadap pesantren di mana kebijakan pesantren disetujui, diterima dan dilaksanakan oleh pranata pemerintah. Penelitian menyimpulkan bahwa sejak dimasukkannya pesantren ke dalam Undang-Undang Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional, maka pesantren berada dalam pusaran tarik menarik kepentingan antara masyarakat dengan Pemerintah. Pesantren diperlakukan diskriminatif oleh Pemerintah ditandai dengan ketidakjelasan implementasi, regulasi dan alokasi anggaran untuk pesantren. Intinya, Pesantren belum mendapatkan perhatian yang seharusnya dari Pemerintah.Kata Kunci: kebijakan, pendidikan, pesantren, Indonesia